KEMISKINAN DAN PENANGGULANGANNYA DALAM SISTEM EKONOMI SYARIAH - Hukmiah Husain (Institut Agama Islam Negeri Bone, 2020)
AbstractPoverty is a complex problem that is faced by all governments is the world. Poverty is a condition in which a person cannot meet their basic needs in order to establish a more dignified life. Therefore, it is mandatory to overcome poverty, because if not, it will be able to disrupt and threaten human survival. In this context, islam came to give some offers methods but able to overcome poverty problems. In islam, there is a transformative thought that favors transformation on social structure through the creation of relation that is fundamentally new and more just it economics, politics, and culture. Islam is a religion that is very concerned about the humanity affairs, in Islamic law the rights of marginal groups (ahlul hajah) are equated with the rights of God. If a government is unable to meet the basic needs of their citizens, they will sow the seeds of destructions through social anxiety and political instability. Among the ways that Islam set to tackle poverty is the creation of a social security system to assign rights for the poor in the wealth of the rich, such as zakat, sadaqah sunnah, and others. Kata kunci: Kemiskinan; Penanggulangannya; Ekonomi Syariah.